Green Approach for Synthesis of Manganese Nanoparticle using Banana Peel (Musa paradiasca) and its Characterization - Amatya, Sharmila Pradhan; Shrestha, Santu; Aryal, Yadav (Amrit Research Journal, 2021)
This research mainly aims at implementing green approach for synthesizing multifunctional manganese nanoparticles (MnNPs) using aqueous extract of banana peel (Musa paradiasca) and potassium permanganate (KMnO4) as the precursor. As synthesized MnNPs were conﬁrmed initially by a color change and later on characterized by UV-visible (UV-vis) Spectrophotometer, Energy Dispersive Spectroscopy (EDX), X-ray Diﬀraction Spectroscopy (XRD) and Fourier Transform Infrared Spectroscopy (FT-IR). Green approach was carried at various parameters like concentration of precursor solution, reaction time, temperature, etc for optimization. The formation of MnNPs was conﬁrmed by the presence of surface plasmon absorbance band (450 nm) and band at 6 and 6.5 keV of EDX spectrum. Likewise, so formed MnNPs were crystalline nature depicted from the sharp peak observed at 28.5º and 41° in X-ray diﬀraction pattern. Various types of biomolecules associated with the banana peel extract acting as natural reducer and stabilizer were analyzed from characteristic absorption bands present in the FT-IR spectrum.